Challenges of Quantifying FODMAPs in Enteral Nutrition Formulas: Evaluation of Artifacts and Solutions. (November 2017) - Halmos, Emma P.; Bogatyrev, Alex; Ly, Elizabeth; Liels, Kelly L.; Muir, Jane G.; Gibson, Peter R.
Background: Diarrhea associated with enteral nutrition has been attributed to excessive FODMAP (fermentable oligosaccharides, disaccharides, monosaccharides, and polyols) content of formulas. This study aimed to readdress their FODMAP content by measuring fermentation-specific effects after a formula load in healthy participants and by defining issues with analytical methods. Methods: Breath hydrogen production expressed as mean area under the curve (AUC) for 12 hours after ingestion of 15 g lactulose or 500 mL of 1 of 2 formulas of seemingly different FODMAP content was evaluated in a double crossover design. Quantification of specified FODMAPs via enzymatic and liquid chromatographic assays was assessed with additional controls to investigate the influence of maltodextrin and sucrose present in the formulas, and alternative assays were applied. Results: In 15 hydrogen-producing participants, AUC following both formulas was minimal (≤21 ppm/12 h) compared with 15 g lactulose ( P < .001). Elevated breath hydrogen was detectable when >2.5 g fructo-oligosaccharide was consumed. Maltodextrin showed dose-dependent interference with enzymatic measurement of fructans and coeluted with raffinose with liquid chromatography. Application of an alternative fructan assay that includes additional enzymes to hydrolyze maltodextrins indicated that fructan content was <15% of that previous reported. Galacto-oligosaccharide (GOS) content could not be estimated by chromatography due to maltodextrins. An enzymatic assay, while overestimating GOS content, showed it to be very low. Conclusion: FODMAPs were not detected in enteral formulas in human bioassays, and their content may be grossly overestimated mainly due to high formula concentrations of maltodextrin. Better estimates of FODMAP content in enteral formulas can be made by alternative assay approaches.